Antiretroviral changes during the first year of therapy - Bandeira,Antonio Carlos Policarpo Carmo Sá (2017)
Summary Introduction: The Brazilian HIV/AIDS management and treatment guideline (PCDT), published in 2013, recommends and standardizes the use of highly active antiretroviral therapy (HAART) in all adult patients, in spite of LTCD4 count. This study aimed to analyze the first year of HAART use in patients from a reference center on HIV/AIDS management in Fortaleza, Ceará. Method: This descriptive study reviewed all prescription forms of antiretroviral regimens initiation and changes from January to July 2014. All antiretroviral regimen changes that occurred during the first year of therapy were evaluated. Data were analyzed with SPSS version 20. Mean, standard deviation and frequency, Student’s t and Mann-Whitney tests calculations were used, with significance at p<0.05. Results: From 527 patients initiating HAART, 16.5% (n=87) had a regimen change in the first year. These patients were mostly male (59.8%; n=52), aged 20 to 39 years, with only one HAART change (72.4%; n=63). Efavirenz was the most often changed drug, followed by tenofovir, zidovudine and lopinavir/ritonavir. Mean time of HAART changes was 120 days, with adverse reactions as the most prevalent cause. HAART was effective in decreasing viral load since second month of treatment (p=0.003) and increasing LTCD4 lymphocytes since fifth month (p<0.001). Conclusion: The main cause of initial HAART changes was adverse reaction and most patients had only one change in the HAART regimen. HAART prescription was in accordance to the PCDT from 2013.